2021
DOI: 10.5194/tc-15-4823-2021
|View full text |Cite
|
Sign up to set email alerts
|

InSAR-based characterization of rock glacier movement in the Uinta Mountains, Utah, USA

Abstract: Abstract. Rock glaciers are a prominent component of many alpine landscapes and constitute a significant water resource in some arid mountain environments. Here, we employ satellite-based interferometric synthetic aperture radar (InSAR) between 2016 and 2019 to identify and monitor active and transitional rock glaciers in the Uinta Mountains (Utah, USA), an area of ∼3000 km2. We used mean velocity maps to generate an inventory for the Uinta Mountains containing 205 active and transitional rock glaciers. These … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 67 publications
1
35
1
Order By: Relevance
“…Only two ARGs have creeping speeds higher than 100 mm•a −1 , and both are moraine-type. The velocity range of ARGs in Daxue Shan is comparable to that in the Uinta Mountains reported by Brencher, Handwerger and Munroe [36]. However, the velocity range is lower than other alpine regions in the Alps, Sierra Nevada, and Northern Tienshan [26,31,34,35].…”
Section: Active Rock Glacier Velocitiessupporting
confidence: 78%
See 2 more Smart Citations
“…Only two ARGs have creeping speeds higher than 100 mm•a −1 , and both are moraine-type. The velocity range of ARGs in Daxue Shan is comparable to that in the Uinta Mountains reported by Brencher, Handwerger and Munroe [36]. However, the velocity range is lower than other alpine regions in the Alps, Sierra Nevada, and Northern Tienshan [26,31,34,35].…”
Section: Active Rock Glacier Velocitiessupporting
confidence: 78%
“…Recent studies have shown that multi-temporal InSAR can reduce SAR phase decorrelation and be used to detect the ARGs with low surface velocities [35]. Brencher, et al [36] compiled 255 ARGs based on multi-year SAR LOS (line-of-sight) displacement velocity in the Uinta Mountains, with a velocity range from 0.88 to 5.26 cm•a −1 , demonstrating the strength of multi-temporal InSAR for ARG mapping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the highly active rock glacier ratio was acquired using a threshold of active rock glacier ratio > 0.1 and monitoring rate > 0.3 (Figure 13 and Table 2). The 75th percentile downslope velocity was another effective indicator used to represent the total deformation velocity of a rock glacier in a recent study [85]. With this indicator, about 4700 rock glaciers showed downslope deformation greater than 100 mm/y (Figure 14c), reporting more active rock glaciers.…”
Section: Comparison With Other Rock Glacier Surface Displacement Studiesmentioning
confidence: 99%
“…More precise and accurate approaches based on remote sensing data (e.g. satellite interferometry with Sentinel-1 images; Yague-Martinez et al, 2016) were developed to characterise the rock glacier kinematics at a large scale (Necsoiu et al, 2016;Wang et al, 2017;Villarroel et al, 2018;Strozzi et al, 2020;Brencher et al, 2021). These latter approaches are nevertheless based on different criteria and still lack standardised outputs (Jones et al, 2018a;Brardinoni et al, 2019), essential to integrate kinematic information in standardised RoGIs.…”
Section: Introductionmentioning
confidence: 99%